Equipment for determining thermoelectric properties of material by modified Harman’s method - Anatychuk , L.I.; Havryliuk, M. V.; Lysko, V.V. (Journal of Thermoelectricity, 2022)
The results of the development of equipment for determining the thermoelectric properties of materials – electrical conductivity, thermal conductivity, the Seebeck coefficient and thermoelectric figure of merit in the temperature range of 30 – 500 °C using modified Harman's method are presented. Measurement errors are estimated and reduction methods are described. The results of measurements of material samples based on Ві2Те3 obtained using the described equipment are shown.